Alterations of the Monoaminergic Systems by Sustained Triple Reuptake Inhibition - Jiang, Jojo L (Université d'Ottawa / University of Ottawa, 2012)
Recent approaches in depression therapeutics include triple reuptake inhibitors, drugs that target three monoamine systems. Using in vivo electrophysiological and microdialysis techniques, the effects of 2- and 14-day treatments of escitalopram, nomifensine and the co-administration of these two drugs (TRI) were examined in male Sprague-Dawley rats. Short- and long-term TRI administration decreased NE firing and had no effect on DA neurons. Normal 5-HT firing rates were maintained after 2-day TRI administration compared to the robust inhibitory action of selective serotonin reuptake inhibitors (SSRIs). Escitalopram treatment enhanced the tonic activation of the 5-HT1A receptors given the increase in firing observed following WAY100635 administration. Nomifensine treatment enhanced tonic activation of the α2–adrenoceptors following idazoxan administration. TRI treatment caused a robust increase in extracellular DA levels that was in part mediated by a serotonergic contribution. Therapeutic effects of the drugs examined in this study may be due to the enhancement of 5-HT, NE and/or DA neurotransmission.
Keywords: Depression; Triple Reuptake Inhibition; In vivo Electrophysiology; Serotonin; Norepinephrine; Dopamine; Microdialysis